The Effect of Government Spending and Investment on the Happiness Level Mediated by the Inequality Level - Rochdianingrum, Widhi Ariestianti; Palupi, Dian; Amanah, Lailatul; Mustika, Hindah (Trunojoyo University of Madura, 2023)
This study aims to examine the role of inequality in mediating the relationship between government spending and investment at the happiness level. Government spending and investment are independent variables. Inequality is the mediating variable while happiness is the dependent variable. This study uses data from 2013 to 2022. This study uses the PLS method to see the relationship between the independent variable and the dependent variable and the role of the mediating variable in mediating the independent variable with the dependent variable. The results showed that investment has a direct and positive relationship with inequality. Government spending does not correlate with the inequality level. The inequality level has no direct influence on the level of happiness. The results of the indirect analysis suggest that inequality cannot mediate the relationship between government spending and investment on the level of happiness. Inequality cannot mediate even though the inequality level tends to decrease. It is because one of the indicators in measuring happiness that has a worsening value, even though other indicators have increased and directly impacted public welfare, is the increasing level of corruption in Indonesia. So, even though inequality tends to improve, corruption is still rampant in this country, and public happiness is decreasing.